Reviews and critiques on learning theories towards proposing a conceptual design model of Assistive Courseware for Low Vision (AC4LV) learners - Aziz, Nurulnadwan; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (2014)
This article reports an ongoing study that intends to propose a Conceptual Design Model of Assistive Courseware which specifically designed for Low Vision (LV) learners. In developing the intended model, learning theories is a part of component that has to be emphasized.So, prior to the development of that model such applicable learning theories should be reviewed.The main objective of this article is to review and critique the learning theories and their implications to the Conceptual Design Model of AC4LV.Thus, in this article five learning theories were reviewed critically and their implications towards the development of proposed model were also discussed. There is no specific methodology applied in this concept article.The researcher applied the existing knowledge to review and critique the previous learning theories.